KECERDASAN EMOSIONAL KEPALA SEKOLAH DAN GURU DALAM MENINGKATKAN PRESTASI PESERTA DIDIK DI SMA AL AZHAR 3 BANDAR LAMPUNG - Ruslan Abdul Gani (UNISAN JURNAL, 2024)
The emotional intelligence of school principals and teachers plays an important role in improving student achievement and creating a conducive learning environment. This research aims to explore the influence of the emotional intelligence of principals and teachers at SMA Al Azhar 3 Bandar Lampung on teacher motivation and performance, as well as interactions and relationships between teachers and students in the learning process. The research method used is qualitative with a case study approach. Data was collected through interviews and observations, then analyzed using content analysis techniques. The results of the research show that the emotional intelligence of the principal has a significant influence on the motivation and performance of teachers at SMA Al Azhar 3 Bandar Lampung. Principals who have high emotional intelligence tend to be able to motivate teachers in their schools better. This can be seen from his ability to understand and respond wisely to various emotional situations that occur at school, as well as providing the emotional support needed by teachers. Apart from that, the principal's emotional intelligence also influences interactions and relationships between teachers and students in the learning process. Emotionally intelligent school principals are able to create positive and harmonious relationships with teachers and students, thereby creating a learning environment that is safe, comfortable and full of self-confidence for students. On the other hand, teachers' emotional intelligence also plays an important role in improving interactions and relationships between teachers and students in the learning process. Emotionally intelligent teachers are able to create positive relationships with students, fellow teachers and other school officials. This can be seen from his ability to understand and respond wisely to students' emotions, as well as collaborating effectively with his colleagues in the teaching team. In order to develop the emotional intelligence of school principals and teachers, it is recommended that they continue to learn and develop themselves. They need to understand and manage their own emotions well, and be able to read and respond wisely to other people's emotions. This will help create a harmonious learning environment, where students feel encouraged to learn and develop optimally.